COMMUNITY-BASED FOREST MANAGEMENT AGREEMENT (CBFMA): THE JUXTAPOSITION OF PARTICIPANTS AND NONPARTICIPANTS BETWEEN BARANGAY POBLACION DISTRICT I AND BARANGAY BACONG, BABATNGON, LEYTE - Gavan, Aira Mae T; Fernandez, Guiraldo C; Bnade, Marlito M; Pogosa, Jimmy O (Journal of Agriculture and Technology Management; Vol 26 No 2 (2023): Vol 26 No 2 (2023): Journal of Agriculture and Technology Management (JATM) Volume 26 July - December 2023 Issue, 2023)
The Community-Based Forest Management Agreement (CBFMA) program, which aims to promote sustainable forest management and conservation, faces challenges in effectively implementing its goals. A qualitative study compared a tenurial holder People’s Organization (PO) in Brgy. Poblacion District I, covered by the CBFMA, with a non-tenurial holder PO in Brgy. Bacong, Babatngon, Leyte, to explore the strides and gaps between them. The Grounded Theory method was employed to understand the existing systems and the relationship of the communities with the forestland. These findings indicate that regardless of the tenurial instrument or lack thereof both communities are aware of the problem of forest degradation and illegal logging and have negative views of these activities. However, the study also reveals that both POs struggle to sustain forest protection in their respective areas. Furthermore, the POs in both communities seem to have a dwindling interest in tree planting and are instead showing a preference for forest patrol activities. This highlights the need for a shift in the approach to forest management and conservation, with greater emphasis on patrolling and enforcement to deter illegal activities. Overall, the study generates a theory by juxtaposing the social forestry governance and mechanisms of each PO from the CBFMA and non-CBFMA sites. The theory suggests that while the CBFMA program has positive aims, there are challenges in implementation that require greater support from national and local government units to ensure effective forest management and conservation.